A Pedagogical Model to Integrate Computational Thinking Logic to First Year Design Studio - ÇETİNEL, MELTEM; GÜZELCİ, ORKAN ZEYNEL (IGI Global, 2021)
Today, computational thinking and computational design approaches transform almost all stages of architectural practice and education. In this context, since students are most likely to encounter computers, in this study, the approach of teaching students computational design logic is adopted instead of teaching how to use computers only as a drafting or representation tool. This study focuses on developing a pedagogical model that aims to teach computational thinking logic and analog computing through a design process. The proposed model consists of four modules as follows: abstraction of music and text (Module 1), decomposition of buildings (Module 2), analysis of body-space (Module 3), design of a space by the help of spatial patterns (Module 4). The proposed model is applied to first-year students in Interior Design Studio in the 2019-2020 fall semester. As a result of Module 4, students designed both anticipated and unanticipated spaces in an algorithmic way.
Keywords: Grammars; Open Source Product; Computer Aided Manufacturing